2017
DOI: 10.3892/br.2017.960
|View full text |Cite
|
Sign up to set email alerts
|

Urate crystals directly activate the T-cell receptor complex and induce T-cell proliferation

Abstract: Abstract. Uric acid is a known danger associated molecular pattern molecule able to induce inflammation following internalization of its crystals by cells of the innate immune system. By activating antigen-presenting cells, urate boosts adaptive immunity as well. Furthermore, urate crystals can induce proliferation of isolated T-cells, which are unable to phagocytose crystal particles. In light of the evidence that urate crystals can also activate dendritic cells and macrophages without prior internalization b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our study demonstrated that purine metabolism was disrupted in the metabolic pathway of aging-induced kidney dysfunction in which the xanthine content was elevated in aging mice. Studies have found that the mechanisms of kidney injury caused by abnormal uric acid increase primarily include oxidative stress, endothelial dysfunction, kidney fibrosis, and inflammation ( 37 40 ). Uric acid is not only a marker of kidney disease but also a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that purine metabolism was disrupted in the metabolic pathway of aging-induced kidney dysfunction in which the xanthine content was elevated in aging mice. Studies have found that the mechanisms of kidney injury caused by abnormal uric acid increase primarily include oxidative stress, endothelial dysfunction, kidney fibrosis, and inflammation ( 37 40 ). Uric acid is not only a marker of kidney disease but also a potential therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…In the apoptotic events that mitigate cancer progression, the changes in mitochondrial function influence cell viability, metabolism, gene expression, mitochondrial membrane permeability, and redox processes (Boland, Chourasia, & Macleod, 2013). The mitochondrial transmembrane potential (MMP, Δψ) was affected by the extrinsic and intrinsic stress stimuli of chemotherapy, which led to cell death, and the formation of the mitochondria permeability transition pore complex, which led to loss of MMP; these changes induce cytochrome c-dependent caspase activation and pro-apoptotic proteins in cancer cells (Eleftheriadis, Pissas, Liakopoulos, & Stefanidis, 2016). In accordance with previous studies, sideroxylin induced the loss of MMP during the cell death process in both cell types in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have shown that uric acid directly activates T cells in an antigen-independent manner. An experiment using human T cells isolated from healthy human blood samples revealed that uric acid not only increased CD25 expression and NRLP3 inflammasome-dependent IL-1␤ secretion but also induced T cell proliferation (27)(28)(29)151). When these observations are taken together, it becomes evident that uric acid alarms the immune system by stimulating dendritic cells, macrophages, and T cells (Fig.…”
Section: Effects Of Uric Acid From Innate To Adaptive Immune Cellsmentioning
confidence: 98%